ChemInform Abstract: Stereodefined Cyclopentanes by Hydroarylation—Ring Opening. Issue 28 (21st June 2013) - Polivkova, Jana; Piotrowski, David W.
Abstract Title compounds are synthesized by ring opening of protected lactams [(IV) and (V), resp.], which are derived from hydroarylation of (I), using a variety of nucleophiles.